Realising the city : Urban ethnography in Manchester - Symons, Jessica; Lewis, Camilla; Atkins, Michael (Book collections on Project MUSE., 2018)
This work explores what happens when a city administration tries to bring their vision for a city into being. It provides ethnographic accounts that complicate the dominant narrative of Manchester's renaissance.